Dampak Penerapan Free Body Diagram Terhadap Kemampuan Peserta Didik Menyelesaikan Soal-soal Hukum Newton dalam Pembelajaran Fisika SMA - Aisyah Mardini; Djusmaini Djamas; Amali Putra (PILLAR OF PHYSICS EDUCATION, 2018)
Multiple representations are recommended for the better understanding of the concepts of physic. One of the concept that we can use is Free Body Diagram (FBD). Free body diagram is a diagram that describes all of the external forces that work on an object in x and y direction. The aim of this research is to examine the influence of the application of free body diagram towards high school students’s abylity to solve physic problems about Newton’s Law. This research used Quasi Experiment Research with Randomized Control-Group Only Design as research design. The population of this research is all of the first grade student of SMA N 14 Padang in 2017/2018 year study. The result of this study showed there is the difference of Mean between sample classes significantly. The coefficient of correlation between the application of free body diagram and high school student’s ability to solve physic problems is about 0,71. It means the correlation is strong. The determination coefficient of this research  is 51,01% or the influence of the treatment is 51,01% toward the ability of student to solve physic problems about Newton’s Law.